Mechanical properties and in vitro degradation behavior of additively manufactured phosphate glass particles/fibers reinforced polylactide - He, Lizhe; Zhong, Jiahui; Zhu, Chenkai; Liu, Xiaoling (2019)
Phosphate glass/polylactide (PG/PLA) composites were additively manufactured via fused deposition modeling. The incorporation of 10 wt % PG particles improved the flexural modulus of composites by ~14% (3.53 GPa) but led to 5% reduction in flexural strength (92.4 MPa). The trend was more pronounced as the particle loading doubled. Comparing to a particulate composite of the same weight fraction, milled PG fibers (PGFs) reinforcement led to more effectively improved flexural modulus (~30%, 4.10 GPa). After 28 days of in vitro degradation in phosphate buffered saline, the particulate composites lost more than 30% of their initial mechanical properties, in contrast to less than 10% reduction of strength/modulus reported from fiber reinforced composites. The additively manufactured PG/PLA matrix composites have potential for application as customized bone fixation plates to repair the fractures under modest load‐bearing applications. © 2019 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48171.